2022
DOI: 10.1029/2022ja030385
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence Statistics of Horse Collar Aurora

Abstract: Horse collar aurora (HCA) are an auroral feature where the dawn and dusk sector auroral oval moves polewards and the polar cap becomes teardrop shaped. They form during prolonged periods of northward interplanetary magnetic field (IMF), when the IMF clock angle is small. Their formation has been linked to dual‐lobe reconnection (DLR) closing magnetic flux at the dayside magnetopause. The conditions necessary for DLR are currently not well‐understood therefore understanding HCA statistics will allow DLR to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 33 publications
8
23
0
Order By: Relevance
“…The difference between the first three datasets, which are based on low-resolution global images, and the last two DMSP datasets where even faint or thin TPAs can be detected, strongly suggest that IMF magnitude, and especially the magnetic energy flux of the solar wind do not influence the occurrence of TPAs, but rather the brightness of the arcs. This is in agreement with results from a recent DMSP study by Bower et al (2022) who found no correlation between TPA occurrence frequency and solar cycle. During solar maximum, CMEs (and thus periods with a high solar wind magnetic energy flux) are much more common than during solar minimum.…”
Section: Imf Magnitude and Magnetic Energy Flux Influence On Tpa Occu...supporting
confidence: 93%
See 3 more Smart Citations
“…The difference between the first three datasets, which are based on low-resolution global images, and the last two DMSP datasets where even faint or thin TPAs can be detected, strongly suggest that IMF magnitude, and especially the magnetic energy flux of the solar wind do not influence the occurrence of TPAs, but rather the brightness of the arcs. This is in agreement with results from a recent DMSP study by Bower et al (2022) who found no correlation between TPA occurrence frequency and solar cycle. During solar maximum, CMEs (and thus periods with a high solar wind magnetic energy flux) are much more common than during solar minimum.…”
Section: Imf Magnitude and Magnetic Energy Flux Influence On Tpa Occu...supporting
confidence: 93%
“…Most of those conjugate dawn-dawn TPA events form during rather weak IMF 𝐴𝐴 𝐴𝐴y . The latter results are similar to the observation from a recently published study by Bower et al (2022). Also, Bower et al (2022) report conjugate TPAs where both arcs appear at dawn during low IMF 𝐴𝐴 𝐴𝐴y values.…”
Section: Dawn-dusk Location Of Conjugate Tpassupporting
confidence: 92%
See 2 more Smart Citations
“…In such cases, a "horse-collar" auroral form is often seen, indicating a teardrop-shaped open flux region (Hones et al, 1989;Elphinstone et al, 1993;Imber et al, 2006;Milan et al, 2020;Bower et al, 2022;. Nevertheless, the assumption of a circular polar cap has been successfully used many times with the ECPC model (e.g., Lockwood et al, 1990;Milan et al, 2017), including an analysis of a full year of data (Milan et al, 2021) and has two major advantages for the present study.…”
Section: Polar Cap Expansion and Contractionmentioning
confidence: 99%